Ciliary propulsion and metachronal coordination in reef coral larvae - Rebecca N. Poon; Timothy A. Westwood; Hannah Laeverenz-Schlogelhofer; Emelie Brodrick; Jamie Craggs; Eric E. Keaveny; Gáspár Jékely; Kirsty Y. Wan (Physical Review Research, 2023)
Larval dispersal is critical to the survival of coral reefs. As the only motile stage of the reproductive cycle, coral larvae choose a suitable location to settle and mature into adult corals. Here, we present a detailed study of ciliary propulsion in the common stony reef coral Acropora millepora. Using high-speed, high-resolution imaging, particle image velocimetry, and electron microscopy, we reveal the arrangement of the densely packed cilia over the larval body surface, and their organization into diaplectic (transversely propagating) metachronal waves. We resolve the individual cilium's beat dynamics and compare the resulting flows with a computational model of a dense ciliary array, and evaluate the efficiency of flow pumping associated with diaplectic metachronism in different regimes.